2020
DOI: 10.3102/0013189x19898700
|View full text |Cite
|
Sign up to set email alerts
|

Social Position or School Participation? Access and Mobilization of Social Capital in a School-Based Network

Abstract: Through school-based networks, parents obtain information, practical help, and other resources. Because networks vary by size and structure, access to these resources is uneven. What accounts for differences in access to social ties and in the mobilization of those ties to provide resources? In this article, we analyze a network of mothers of eighth graders at a Philadelphia public school. With a near-complete census of network ties, we explore mothers’ access to and mobilization of information and practical h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Schools, like day care centers (Small 2009), are key anchors of parents’ social ties. This insight has practical implications for how school administrators may foster durable connections among parents, many of which lay dormant and are not activated for the exchange of resources (Quinn et al 2020). How might school leaders bolster parent networks?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Schools, like day care centers (Small 2009), are key anchors of parents’ social ties. This insight has practical implications for how school administrators may foster durable connections among parents, many of which lay dormant and are not activated for the exchange of resources (Quinn et al 2020). How might school leaders bolster parent networks?…”
Section: Discussionmentioning
confidence: 99%
“…How might school leaders bolster parent networks? Research has demonstrated an association between parent networks and involvement in school activities (Li and Fischer 2017; Quinn et al 2020). Schools may strive to establish practices and design events that not only facilitate parents’ connections with other parents but also foster relationships that parents can draw on to obtain and provide resources (see Shoji et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation